DEVELOPMENT OF STUDENTS' SPEECH AND LINGUISTIC SKILLS THROUGH DIGITAL TECHNOLOGIES - Sanobar Kuldasheva (Web of Journals Publishing, 2025)
The article discusses the effective use of multimedia tools in native language lessons, requirements for creating multimedia technologies and tasks, and their implementation. The opinions of scholars and methodologists are analyzed.
Keywords: Virtual world, cyber pedagogy, multimedia technology, animation, video, activity approach.